2023
DOI: 10.11606/s1518-8787.2023057005628
|View full text |Cite
|
Sign up to set email alerts
|

Birth-to-childhood tracking of linear growth and weight gain in the MINA-Brazil Study

Bárbara Hatzlhoffer Lourenço,
Caroline Zani Rodrigues,
Ana Alice de Araújo Damasceno
et al.

Abstract: OBJECTIVE: To investigate birth-to-childhood tracking of linear growth and weight gain across the distribution of length/height and weight for age z-scores and according to household wealth. METHODS: Data from 614 children from the MINA-Brazil Study with repeated anthropometric measurements at birth and up to age five years were used. Z-scores were calculated for length/height (HAZ) and weight (WAZ) according to international standards. Birth-to-childhood tracking was separately estimated using quantile regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…The prospective monitoring of growth from birth to five years of age showed that, although mean weight and height resulted in nutritional status indicators close to reference medians, malnutrition and overweight coexisted in the study population. The dynamics of nutritional status in these children points to the low probability of the spontaneous reversal of adversely affected growth patterns, especially during pregnancy and in the first two years of life 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prospective monitoring of growth from birth to five years of age showed that, although mean weight and height resulted in nutritional status indicators close to reference medians, malnutrition and overweight coexisted in the study population. The dynamics of nutritional status in these children points to the low probability of the spontaneous reversal of adversely affected growth patterns, especially during pregnancy and in the first two years of life 4 .…”
mentioning
confidence: 99%
“…O monitoramento prospectivo do crescimento a partir do nascimento até os 5 anos de idade mostrou que, a despeito do peso e a estatura médias resultarem em indicadores de estado nutricional próximos às medianas de referência, desnutrição e sobrepeso coexistem na população do estudo. A dinâmica do estado nutricional observada entre as crianças aponta para a baixa probabilidade de reversão espontânea de padrões de crescimento adversamente afetados, especialmente durante a gestação e nos dois primeiros anos de vida 4 .…”
unclassified